Pride parades and prejudice: Visibility of Roma and LGBTI communities in post-socialist Europe. Issue 3 (September 2016) - McGarry, Aidan
Abstract: This article argues that public space is important for marginalised communities in order to ensure visibility and presence in public life. Often minority groups are excluded from democratic procedures which favour majority interests and preferences. This is not to say that minority interests are incompatible with those of the majority but some marginalised groups are not anchored in public space, can suffer discriminatory treatment and lack the ability to control dominant, usually negative, ascriptions of group identity. This article explores two cases of marginalised communities and access to public space in post-socialist Europe: Roma and the LGBTI communities. Both communities have attempted to ensure their presence in public space through 'Pride' parades across Central and Eastern European capitals. The purpose of pride parades is to demand rights as citizens, such as equality and respect, and to ensure visibility in public life. On the one hand, visibility is important for LGBTI communities who remain relatively hidden and fear 'coming out'. On the other hand, for Roma, who are highly visible, pride offers an opportunity to harness this visibility to challenge prevailing negative stereotypes through an affirmation of group identity.